A.04 Anatomic variation of the Circle of Willis in perinatal stroke. (17th June 2016) - de Jesus, PN; Mineyko, A; Kirton, A; Yu, S
Abstract : Background: Perinatal stroke is a common disorder in neonates with unknown etiology. Previous studies have linked anatomic variations in the Circle of Willis to adult stroke. This study aimed to understand the potential relationship between circle anatomy and common forms of perinatal stroke: NAIS, APPIS, and PVI.Methods: 94 subjects (62 NAIS/APPIS, and 32 PVI) were identified from the Alberta Perinatal Stroke Project. Inclusion criteria were: MRI-confirmed perinatal stroke, 3D-TOF MRA, and absence of other disorders. Images were classified as complete, incomplete posterior circulation, incomplete anterior circulation, and incomplete anterior and posterior circulation. Fisher Exact Test compared completeness against stroke type and segment absence ipsilateral to stroke. Mann-Whitney U compared completeness and lesion volume.Results: Completeness was more common in PVI than NAIS/APPIS (p=0.500) and in healthy controls than total stroke population (p=0.251). Ipsilesional absent segments were more frequent in NAIS/APPIS (p= 0.270). NAIS/APPIS patients with complete CoW had larger median lesion volume was compared to those with incomplete circles (p=0.484), with contralateral absence (p=0.943), and with ipsilateral absence (p=1.00). The opposite was found in PVI patients for all lesion volume comparisons (p=0.321, 0.362, 0.739 respectively).Conclusions: Circle anatomy is highly variable in perinatal stroke. Absence of segments is not associated with stroke type, lesion side, and lesion volume.